BUSINESS RISK MANAGEMENT: FEATURES AND PROBLEMS IN SMALL AND MEDIUMSIZED TRADING AND MANUFACTURING ENTERPRISES - Larisa Belinskaja; Margarita Velickiene (European Scientific Journal, ESJ, 2015)
SMEs are generally recognised as the engine of economic development, and their development becomes a precondition for the international competitiveness and the economic growth of the state. Business risk management is a specific management sphere that requires a deep understanding of economic activity, decision optimisation, insurance activities, and knowledge of economics, law, psychology and many other fields. In countries with deep-rooted business traditions, business risk management starts with the creation of the company. Currently Lithuania has no consensus on how to encourage and support the entrepreneurship in SMEs, minimizing the danger of possible risk. The main research tasks of the article are as follows: we analyse the related literature and information about SME risk management, and its application, generalizing this topic, and then we examine and evaluate the practical applications of business risk management instruments to SME companies in trading and manufacturing sectors in Lithuania. The data analysis of empirical studies carried out with the managers and experts of the Lithuanian SMEs, using the survey and interview methods, revealed a greatly varying capacity of the respondents to identify business risk and manage it accordingly. Such differences are particularly noticeable when examining SME CEOs understanding of what risk mitigation instruments can be applied to their business.